HOW GAY MEN PREPARE FOR DEATH The Dying Business - Robinson, Peter (Emerald Publishing, 2023)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online. Peter Robinson's new book provides a practical contribution for anyone considering how to prepare for their end of life, including those from LGBTQ+ communities.